Compressive Strength and Solubility/ Sorption Behavior of Conventional Zinc Phosphate Cement and Zinc Phosphate Cement Containing Sodium Free Bioactive Glass An in vitro study - Sanjana Kalra 20D02104; Dr Nanditha Kumar (JSS AHER, Mysuru JSSDCH, Mysuru, 2020)
01.Introduction 02.Aims & Objectives 03.Review of Literature 04.Methodology 05.Results 06.Discussion 07.Conclusion 08.Summary 09.References 10. Annexure